Microbiological and Serological Investigation of Periodontal Disease Activity - KOHYAMA, Akira (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1989)
If disease activity in periodontal disease can be determined, the therapeutic measures of periodontitis may become diverse and different from patient to patient. The purpose of the present study was to evaluate the usefullness of microbiological and serological examination of periodontopathic bacteria in detecting destructive periodontal disease activity. One hundred and forty-eight sites in 52 subjects with moderate to severe periodontitis were studied clinically. Clinical parameters included plaque index, gingival index, probing depth, bleeding on probing and percent bone loss as measured radiographically. Subgingival plaque of whole sites was investigated microbiologically by means of indirect fluorescentantibody technique with rabbit antibodies against Actinomyces viscosus, Actinobacillus actinomycetemcomitans (2 serotypes), Eikenella corrodens, Fusobacterium nucleatum, Bacteroides gingivalis and Bacteroides intermedius. The levels of serum IgG antibody to these organisms were determined by enzyme-linked immunosorbent assay with whole cell prepartions. Thirty-two of 52 subjects were instructed in oral hygiene and received several sessions of scaling and root planing. The clinical, bacteriological and serological assessments were also performed after periodontal therapy. Active disease site was defined as the site of which clinical status did not be improved even after periodontal treatment. B. gingivalis, B. intermedius and A. viscosus were detected in 80% of periodontal lesions, and the proportion of B. gingivalis was the highest among six bacterial species tested. A. actinomycetemcomitans, E. corrodens and F. nucleatum were found only occasionally and in low numbers. The proportion of B. gingivalis was higher in severely inflamed sites than in clinically healthy sites. B. gingivalis and B. intermedius are rarely found in treated periodotitis sites, while the proportion of A. viscosus was slightly increased after theatment. Sera of the pre-treatment patients demonstrated significantly higher antibody levels to B. gingivalis and significantly lower levels to A. viscosus than those of healthy persons. Antibody levels reactive with other four species in the patients did not significantly differ from the levels in healthy persons. After periodontal therapy, antibody levels to B. gingivals, B. intermedius and A. actinomycetemcomitans(serotype a) significantly decreased and the levels to A. viscosus increased to a slight degree. B. gingivalis was found more frequently in diseaseactive sites than in disease-inactive sites. The proportions of other bacterial species in disease-active sites did not differ from those in disease-inactive sites. The results of the present investigation suggest that monitoring B. gingivalis in subgingival plaque and serum IgG antibody titer against this organism may aid in the description and adequet treatment of the periodontal disease.